Role of the endothelium in modulating sympathetic vasoconstriction in contracting skeletal muscle of young and older adults - Hearon, Christopher M., author; Dinenno, Frank A., advisor; Amberg, Gregory, committee member; Chicco, Adam, committee member; Gentile, Christopher, committee member (Colorado State University. Libraries, 2016)
Aerobic capacity is a powerful independent predictor of all-cause mortality in healthy and disease populations. Healthy (primary) ageing is associated with a decline in maximal aerobic capacity, exercise intolerance and elevated risk for ischemic cardiovascular disease. Specifically, ageing is characterized by impaired regulation of vascular tone during exercise, due in part to lower vasodilatory signaling and elevated sympathetic vasoconstrictor activity in the peripheral vasculature. Impaired regulation of peripheral vascular tone results in attenuated blood flow and oxygen delivery to contracting skeletal muscle during exercise and is a primary contributor to the age-associated decline in aerobic capacity. The overall aim of this dissertation is to determine the vascular signaling mechanisms responsible regulating sympathetic vasoconstrictor signaling during exercise in young healthy adults and translate these findings to improve vascular function during exercise in older adults. The regulation of blood flow and oxygen delivery during exercise depends on the proper integration of local vasodilatation and neural sympathetic vasoconstriction. In healthy humans, the integration of these competing signals results in attenuation of sympathetic vasoconstriction, or “sympatholysis”, to ensure adequate blood flow to contracting skeletal muscle. The signaling mechanisms responsible for sympatholysis in healthy humans are unknown. To date, the only exogenous vasodilator shown to mimic exercise in its ability to attenuate sympathetic vasoconstriction in humans is adenosine triphosphate (ATP). The first aim of this dissertation is to determine if smooth muscle cell hyperpolarization (via activation of inwardly-rectifying potassium (KIR) channels), the primary vasodilatory pathway of ATP, is responsible for ATP-mediated attenuation of sympathetic vasoconstriction. In contrast to smooth muscle specific signaling, vasodilatory stimuli such as ATP and exercise can act through endothelium-dependent pathways. The second aim of this dissertation tests the hypothesis that endothelium-dependent signaling is capable of attenuating sympathetic vasoconstriction during exercise in young healthy humans. With age, impaired endothelial function and elevated sympathetic vasoconstrictor activity results in impaired functional sympatholysis. The third aim is to determine if augmentation of endothelium-dependent signaling during exercise improves age-associated impairments in functional sympatholysis. The primary findings of this dissertation are that 1) similar to exercise, the ability of ATP to attenuate sympathetic vasoconstriction is independent of smooth muscle cell hyperpolarization via activation of KIR channels, 2) activation of endothelium-dependent signaling during exercise significantly enhances the ability of contracting skeletal muscle to attenuate sympathetic vasoconstriction, and 3) that augmentation of endothelium-dependent signaling during exercise significantly improves functional sympatholysis in older adults. These findings are the first to identify endothelium-dependent modulation of sympathetic vasoconstriction in humans, and identifies vascular signaling pathways capable of improving the regulation of vascular tone during exercise in older adults. These findings are clinically significant for patient populations and disease states characterized by impaired functional sympatholysis including ageing, hypertension, and heart failure.